Joint Source-Channel Coding and Channelization for Embedded Video Processing With Flash Memory Storage - Li, Yiran; Dong, Guiqiang; Zhang, Tong (IEEE transactions on signal processing, 2012)
This paper presents a joint source coding, channel coding, and flash memory channelization design framework to obtain optimized tradeoffs among energy consumption, bit rate, and end-to-end distortion (i.e., optimal E-R-D tradeoff space) for embedded and mobile devices with limited power source and abundant flash memory storage capacity. The optimal E-R-D tradeoff space enables embedded and mobile devices to cohesively optimize the source coding and data storage system operations subject to run-time power source, storage capacity, and/or distortion constraints. By treating flash memory as a communication channel, this work differs from classical joint source-channel coding from two perspectives: i) Classical joint source-channel coding aims to obtain an optimized R-D (bit rate and distortion) tradeoff space, while we aim to obtain an optimized E-R-D tradeoff space; ii) Flash memory can be configured (or channelized) over an energy consumption versus raw bit error rate tradeoff spectrum, and channelization is an integral part of the joint design. With the focus on video coding, this paper presents theoretical investigations and specific approaches for both scenarios where channel can and cannot contribute to end-to-end distortion. Based on detailed power estimation and representative video sequences, we quantitatively demonstrate the application of the proposed design approaches for obtaining optimized E-R-D tradeoff space.